Efficacy and safety of selective laser trabeculoplasty for uveitic glaucoma - Minako Suzuki; Masaki Takeuchi; Akira Meguro; Jutaro Nakamura; Mamoru Tateishi; Miki Fukuda; Akihiro Kamata; Yuki Mizuki; Kayoko Yamada; Etsuko Shibuya; Norihiro Yamada; Mami Ishihara; et al. (Scientific Reports)
Abstract To determine the efficacy and safety of selective laser trabeculoplasty (SLT) in patients with uveitic glaucoma, we retrospectively evaluated 17 eyes from 13 consecutive uveitic glaucoma cases who were treated with SLT due to inadequate interocular pressure (IOP) control despite glaucoma medical therapy. The mean IOP was significantly decreased from 28.4 ± 6.50 mmHg to 17.3 ± 9.4 mmHg at baseline, and 6 months after SLT, respectively (P < 0.0001). There was no significant increase in inflammation or prednisolone dosage following SLT. We compared the success group, which demonstrated successful IOP reduction after 6 months of SLT, to the other failure group. The success group had shorter uveitis duration (1.37 ± 0.41 vs. 1.97 ± 0.80 years, P = 0.032) and lower baseline IOP (25.5 ± 5.09 vs. 33.7 ± 5.57 mmHg, P = 0.035). This study found that SLT had a positive IOP-lowering effect and was safe in patients with uveitic glaucoma who had not responded to medical treatment.